Expression of Ascaris lumbricoides putative virulence‑associated genes when infecting a human hos - Norashikin, Mohd‑Shaharuddin; Yvonne Lim, Ai Lian; Romano, Ngui; Sheila, Nathan (BioMed Central Ltd., 2021)
Background: Ascaris lumbricoides is the most common causative agent of soiltransmitted helminth infections worldwide, with an estimated 450 million people infected with this nematode globally. It is suggested that helminths are capable of evading and manipulating the host immune system through the release of a spectrum of worm proteins which underpins their longterm survival in the host. We hypothesise that the worm overexpresses these proteins when infecting adults compared to children to cirvumvent the more robust defence mechanisms of adults. However, little is known about the parasite’s genes and encoded proteins involved during A. lumbricoides infection. Hence, this study was conducted to assess the expression profle of putative virulenceassociated genes during an active infection of adults and children. Methods: In this study, quantitative PCR was performed to evaluate the expression profle of putative virulence associated genes in A. lumbricoides isolated from infected children and adults. The study was initiated by collecting adult worms expelled from adults and children following anthelminthic treatment. Highquality RNA was successfully extracted from each of six adult worms expelled by three adults and three children, respectively. Eleven putative hom‑ ologues of helminth virulenceassociated genes reported in previous studies were selected, primers were designed and specifc amplicons of A. lumbricoides genes were noted. The expression profles of these putative virulenceassoci‑ ated genes in A. lumbricoides from infected adults were compared to those in A. lumbricoides from infected children. Results: The putative virulenceassociated genes VENOM, CADHERIN and PEBP were signifcantly upregulated at 166 fold, 13fold and fvefold, respectively, in adults compared to children. Conversely, the transcription of ABA-1 (fourfold), CATH-L (threefold) and INTEGRIN (twofold) was signifcantly suppressed in A. lumbricoides from infected adults.